Tinjauan Hukum Mengenai Unsur Kelalaian Dalam Kematian Ternak Sapi di Desa Laerung: Analisis Yuridis-Empiris Berdasarkan Perbuatan Melawan Hukum - Ismail Ali; Faizal Pratama; Dian Sabrina; Yuliani (Legal Journal of Law, 2026)
This study aims to evaluate the manifestation of negligence (culpa) in cattle deaths in Laerung Village through the lens of Articles 1365 and 1367 of the Civil Code (KUHPerdata). Livestock deaths in rural areas are often viewed as ordinary agricultural incidents, but legally, they carry significant complexities of civil liability. Using empirical legal research methods, this study identifies that the ambiguity of the boundaries between "accidental acts" and "gross negligence" is a primary trigger for disputes between residents. The findings indicate that the lack of specific local regulations regarding grazing zoning exacerbates the degree of negligence of both livestock owners and third parties. In addition to negligence (culpa), the mysterious and mass deaths occurring within a short period of time strengthens the suspicion of intentional (dolus) action by another party, based on police reports. This research's original contribution lies in integrating formal legal norms with the sociological realities of rural communities in establishing standard parameters for the duty of care in the smallholder livestock sector.